2018
DOI: 10.1039/c8nr07453d
|View full text |Cite
|
Sign up to set email alerts
|

Nanoclusters of crystallographically aligned nanoparticles for magnetic thermotherapy: aqueous ferrofluid, agarose phantoms andex vivomelanoma tumour assessment

Abstract: An integrated approach to advance in the translation of magnetic hyperthermia to clinical uses is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 59 publications
5
26
0
Order By: Relevance
“…Studies have shown that the temperature above 43 °C could induce cancer cell apoptosis, while the temperature exceeding 45 °C could generate hyperthermia to induce tumor ablation. [ 31 ] As expected, only a maximum temperature of 2 °C was increased in the tumor sites treated with blank MNs ( Figure ), which showed neglectable curative effect in inhibiting tumor growth. Encouragingly, the temperature of the tumor sites treated with PTNPs (PTX/ICG) or PTNPs (ICG) loaded MNs increased quickly to 48 °C within 1 min and kept stable in the next 4 min, which confirmed the good photothermal conversion efficiency of ICG loaded MNs and showed the potential of damaging cancer cells in vivo.…”
Section: Resultssupporting
confidence: 58%
“…Studies have shown that the temperature above 43 °C could induce cancer cell apoptosis, while the temperature exceeding 45 °C could generate hyperthermia to induce tumor ablation. [ 31 ] As expected, only a maximum temperature of 2 °C was increased in the tumor sites treated with blank MNs ( Figure ), which showed neglectable curative effect in inhibiting tumor growth. Encouragingly, the temperature of the tumor sites treated with PTNPs (PTX/ICG) or PTNPs (ICG) loaded MNs increased quickly to 48 °C within 1 min and kept stable in the next 4 min, which confirmed the good photothermal conversion efficiency of ICG loaded MNs and showed the potential of damaging cancer cells in vivo.…”
Section: Resultssupporting
confidence: 58%
“…1 Specifically, SPIONs are used as longitudinal 2,3 and transverse magnetic resonance imaging (MRI) contrast agents, 4 in cell labeling, 5 cell sorting 6 or cell therapy, 7 as drug delivery carriers 8 and in thermotherapy for oncological treatments. 9,10 The efficiency of iron oxide nanoparticles for the intended application as well as the particles fate will largely depend on how the nanoparticle surface interacts with the proteins present in a given physiological environment. In a bio-relevant milieu, the formation and time evolution of the protein corona resulting from the biomolecules adsorption on the nanoparticles surface can be extremely diverse and dynamic over time.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperthermia‐Based Therapy : The heat generation by ferromagnetic particles is based on two steps, namely, relaxation and hysteresis loss . When an alternating magnetic field is applied, the magnetic moment changes its original orientation and rubs against the crystal lattice (internal friction, Neel relaxation).…”
Section: Ferrofluid‐based Detection Diagnosis and Therapymentioning
confidence: 99%